Therapeutic Response and Long-term Outcome of Differentiated Thyroid Cancer with Pulmonary Metastases Treated by Radioiodine Therapy (Bangladesh Journal of Nuclear Medicine, 2022)
Objective: This retrospective study was conducted to assess the efficacy of radioactive iodine therapy (RAIT) and investigate the prognostic factors for patients with pulmonary metastasis from differentiated thyroid carcinoma (DTC).Materials & Methods: A total of 80 patients treated with radioactive iodine (131I)-avid pulmonary metastasis from DTC treated with 131I from 2001 to 2016 at National Institute of Nuclear Medicine & Allied Sciences (NINMAS) were enrolled in this study. Treatment response was mainly measured by serum thyroglobulin (Tg) levels, diagnostic 131I whole-body scan (DxWBS) and patients clinical response. According to the treatment response patients were classified in two groups-complete response (CR) and persistent disease (PD).Result: Among 80 patients; 53(66.25%) males and 27(33.75%) females. Six patients were lost to follow-up; this study was done on the rest 74 patients. Out of 74 patients according to histological pattern 65(87.84%) were PTC and FTC 09(12.16%). Among 74 patients 50 had LN metastases; lung metastases were in 18 cases and six patients showed both lungs and bone metastases initially. RxWBS revealed lung metastasis in all of these 74 patients. The average received a dose of 131I was 537 ± 17.6 m Ci. Average postoperative serum Tg level at the time of presentation at NINMAS was 97.3 ng/ml with a decline in serum Tg levels after RAIT to 90 ng/ml. In the case of CR 14 patients showed diffuse lung uptake and 13 showed focal uptake; among PD 40 patients showed diffuse uptake and 14 showed focal lung uptake (p-value-0.004). The average follow-up period was 06 years. We observed CR in 25 (33.78%) patients and PD in 49 (66.21%) patients. The patient with CR; their an initial Tg level average of 38.9 ng/ml and after receiving last therapy their follow-up average Tg was 1.9 ng/m (p value-0.001). For the patient who had PD, their initial Tg level was 126.2 ng/ml, follow up average Tg was150 ng/dl with rising Tg level.Conclusion: From this study, it may be concluded that patients with DTC with lung metastases, most of the patients showed persistence of disease (66.21%) even after giving repeated radioiodine therapy. DxWBS and serum Tg levels at diagnosis are both important factors to evaluate the therapeutic response. Patients presenting with high serum Tg at initial diagnosis and subsequent bony metastases are likely to show a poor outcomeBangladesh J. Nuclear Med. 24(1&2): 42-47, 2021